Assessing the unified airway hypothesis in children via transcriptional profiling of the airway epithelium - Kicic, Anthony; de Jong, Emma; Ling, Kak-Ming; Nichol, Kristy; Anderson, Denise; Wark, Peter A.B.; Knight, Darryl A.; Bosco, Anthony; Stick, Stephen M.; Kicic, Anthony; Stick, Stephen M.; Knight, Darryl A.; et al. (Journal of allergy and clinical immunology, 2020)
Emerging evidence suggests that disease vulnerability is expressed throughout the airways, the so-called unified airway hypothesis, but the evidence to support this is predominantly indirect. We sought to establish the transcriptomic profiles of the upper and lower airways and determine their level of similarity irrespective of airway symptoms (wheeze) and allergy. We performed RNA sequencing on upper and lower airway epithelial cells from 63 children with or without wheeze and accompanying atopy, using differential gene expression and gene coexpression analyses to determine transcriptional similarity. We observed approximately 91% homology in the expressed genes between the 2 sites. When coexpressed genes were grouped into modules relating to biological functions, all were found to be conserved between the 2 regions, resulting in a consensus network containing 16 modules associated with ribosomal function, metabolism, gene expression, mitochondrial activity, and antiviral responses through IFN activity. Although symptom-associated gene expression changes were more prominent in the lower airway, they were reflected in nasal epithelium and included IL-1 receptor like 1, prostaglandin-endoperoxide synthase 1, CCL26, and periostin. Through network analysis we identified a cluster of coexpressed genes associated with atopic wheeze in the lower airway, which could equally distinguish atopic and nonatopic phenotypes in upper airway samples. We show that the upper and lower airways are significantly conserved in their transcriptional composition, and that variations associated with disease are present in both nasal and tracheal epithelium. Findings from this study supporting a unified airway imply that clinical insight regarding the lower airway in health and disease can be gained from studying the nasal epithelium. [Display omitted]